Budowa geologiczna rejonu szybika Tesch w Kopalni Soli Bochnia w świetle nowych danych - Żerańska, Kamila (My University, 2011)
The ‘Bochnia’ salt deposit is located at the front of the Carpathian overthrust, in the miocen’s fold zone. It is a very valuable property to the observation of changes in geological structure of the deposit, which is the result of strong commitment to tectonic and geotectonic and contemporary movements. Conducted observations and analysis of selected elements of the geological structure in the pit’s ‘Tesch’ area led to a detailed description of lithostratigraphy and tectonics of this part of the deposit. Laboratory tests of samples of eleven tracks of evaporites and the pattern of the geological structure through the salt deposit around the ‘Tesch’ stairs, which was drawn based on 148 photographs of the mine’s walls, were the primary source of data of this study. The salt deposit in the pit’s ‘Tesch’ area has complicated internal tectonics and relatively monotonous lithostratigraphic structure.

Złoże soli kamiennej Bochnia zlokalizowane jest przy brzegu Karpat, w strefie miocenu sfałdowanego. Stanowi bardzo cenny obiekt do obserwacji zmian w budowie geologicznej złoża, będącej efektem silnego zaangażowania tektonicznego oraz geotektonicznych i współczesnych ruchów. Przeprowadzone obserwacje i analiza wybranych elementów budowy geologicznej w rejonie szybiku Tesch pozwoliły na szczegółowy opis litostratygrafii i tektoniki tej partii złoża. Badania laboratoryjne jedenastu próbek utworów solnych oraz sporządzenie na podstawie 148 fotografii ociosu, schematu budowy geologicznej przez złoże soli kamiennej w okolicy schodów Tesch, stanowiły podstawowe źródło danych niniejszej pracy. Złoże w rejonie szybiku Tesch charakteryzuje skomplikowana tektonika wewnętrzna oraz stosunkowo monotonne wykształcenie litostratygraficzne.
The geological structure of the pit's ‘Tesch’ region Bochnia salt mine in the light of new data
Keywords: zapadlisko przedkarpackie; miocen; geologia złoża; szybik; ewaporaty; Carpathian Foredeep; Miocene; geology of deposits; pit; evaporites